Analytical study of a repair methodology for flexible pipes anti-birdcage tapes. (January 2019) - Li, Xiaotian; Vaz, Murilo Augusto; Custódio, Anderson Barata
Abstract: Flexible pipes may be exposed to high risk of birdcage failure mechanism if the anti-birdcage tapes are damaged. A feasible repair methodology has been proposed by winding multi-layers of high strength filaments with specific pre-tension over the damaged area and its neighboring regions. To investigate the mechanism of this repair technique, an analytical model is developed by simplifying the problem as superimposed tape and filaments over an expandable frictional cylindrical surface. Through which, the effects of the pivotal parameters regarding this repair technique, including the geometrical and material properties of the filaments, pre-tension in the filaments, number of filamentous layers, as well as the length of the repaired section surpassing the damaged region on both sides, on the effectiveness of this repair methodology are investigated extensively. In addition, the effectiveness of this repair methodology in the long term is evaluated considering the potential pre-tension reduction phenomenon of the filaments. A series of case studies are performed and some useful suggestions are presented in view of this repair methodology. Highlights: A repair methodology for damaged anti-birdcage tape in flexible pipe is addressed. An analytical model is formulated to investigate the mechanism of this repair method. The influence of some pivotal parameters on the repair effectiveness is discussed. Pre-tension reduction effect of the filaments used in this repair method is assessed.